If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9*ln(4/3)-ln(4) = 8*ln(4)-(9*ln(3))
9*ln(3/4)-ln(4)
(3/5)*x^15
108.65/14
e^(2*t)*cos(2*t)
| 4x=2x-15 | | x^2-x-2.25=0 | | 5=x^2*x | | 3=x^2*x | | 6/x^2=0 | | 4x-(8x+7)=8x-9 | | 16/7÷8/49 | | -7(x+1)-17=16+2 | | 2x+135=8x-9 | | (x-15)+(x-15)=(x+7) | | 33/12•12/11 | | 37200= | | 9ln(4/3)-ln(4)=8ln(4)-9ln(3) | | -11x-5x=42 | | 4y+3=-12 | | 0.4q+3.2=7.6-0.7q | | (625)(25)=x | | 0.4q+3.2=7.6-0.7 | | 22(x+2)=24(x-2) | | 2z+16=180 | | 2x-25=23 | | 3=16x^2-46 | | 21=w/2-12 | | a=5+3n-1 | | 9xy/9xy | | 9(x+8)-3(7x-7)=19 | | -3+-5n+na=0 | | 9(4x-8)=3(12x+2) | | 20t+40-6t=10t-47+35 | | -(5x-2)+3x-8=-6 | | 21x^2-86x+80= | | 1a-6=8-(9+a) |